Economic estimation of coral reef ecosystem utilization in Maitara island waters Tidore City islands - Hi. Kader, Iwan; Alhadad, M. Said (Agrikan Jurnal Agribisnis Perikanan, 2022)
Coral reefs are a group of coral animals that live in symbiosis with a type of algae called zooxanthellae. Coral reefs themselves have functions and benefits as well as very important meaning for human life both in terms of economy and as a support for tourism activities. This study aims to estimate the economic value of using coral reef ecosystems on Maitara Island, seen from the value of direct benefits as fishing grounds, value of coral mining, tourism value and research value and estimating the value of indirect benefits as the manufacture of breakwaters and spawning areas. (nursery ground). Based on the results of the study, the actual condition of coral reef ecosystem resources in the waters of Maitara Island, Tidore Island City with an area of 17.55 Ha, has an economic value of direct use of coral reef ecosystems during 2019 of Rp. 14,762,522,910, which consists of a fishery benefit value of Rp. 6,858,991,660, the value of coral mining is Rp. 1,485,000,000, tourism value Rp. 12.060.000 and research value Rp. 5,850,000. While the indirect benefit value of coral reefs on Maitara Island in 2019 was Rp. 6,400,621,250, which consists of making a wave barrier of Rp. 6,380,000,000 and the value of the nursery ground is Rp. 20,621,250.